Adenovirus Viral Kinetics and Mortality in Ex Vivo T Cell-Depleted Hematopoietic Cell Transplant Recipients With Adenovirus Infection From a Single Center. (6th May 2020) - Lee, Yeon Joo; Fang, Jiaqi; Zavras, Phaedon D; Prockop, Susan E; Boulad, Farid; Tamari, Roni; Perales, Miguel Angel; Papadopoulos, Esperanza B; Jakubowski, Ann A; Giralt, Sergio A; Papanicolaou, Genovefa A
Abstract: Background: We report on predictors of adenovirus (ADV) viremia and correlation of ADV viral kinetics with mortality in ex vivo T-cell depleted (TCD) hematopoietic cell transplant (HCT). Methods: T cell-depleted HCT recipients from January 1, 2012 through September 30, 2018 were prospectively monitored for ADV in the plasma through Day (D) +100 posttransplant or for 16 weeks after the onset of ADV viremia. Adenovirus viremia was defined as ≥2 consecutive viral loads (VLs) ≥1000 copies/mL through D +100. Time-averaged area under the curve (AAUC) or peak ADV VL through 16 weeks after onset of ADV viremia were explored as predictors of mortality in Cox models. Results: Of 586 patients (adult 81.7%), 51 (8.7%) developed ADV viremia by D +100. Age <18 years, recipient cytomegalovirus seropositivity, absolute lymphocyte count <300 cells/µL at D +30, and acute graft-versus-host disease were predictors of ADV viremia in multivariate models. Fifteen (29%) patients with ADV viremia died by D +180; 8 of 15 (53%) died from ADV. Peak ADV VL (hazard ratio [HR], 2.25; 95% confidence interval [CI], 1.52–3.33) and increasing AAUC (HR, 2.95; 95% CI, 1.83–4.75) correlated with mortality at D +180. Conclusions: In TCD HCT, peak ADV VL and ADV AAUC correlated with mortality at D +180. Our data support the potential utility of ADV viral kinetics as endpoints in clinical trials of ADV therapies. Abstract : Adenovirus viral burden was examined as predictors of mortality in multivariate models. Adenovirus time-averaged area under the curve (AAUC) and peak adenovirus viral load were independent predictors for mortality in ex vivo T cell-depleted hematopoietic cell transplant recipients.